Correlações fenotípicas entre características de produção e crescimento em genótipos de bananeira - Ramos, Dayana Portes [UNESP] (2009)
The correlations between the characters seen in experimental trials are generated by genetic and environmental factors and are estimated for the purpose of measuring the change in a character when the selection is practised in another. The objective was to correlate bunch weight with characteristics of growth and production of 4 genomic groups of banana: 'Nanicão-IAC-2001', 'Grand Naine', 'Caipira' and 'Nam' (AAA); 'Maçã', 'Thap Maeo', 'Prata Anã' and 'Prata Zulu' (AAB), 'Fhia 01', 'Fhia 18', 'Prata Graúda' and 'Maçã Tropical' (AAAB) and 'Figo Cinza' (ABB), Botucatu, Brazil. Some growth characteristics were evaluated such as: plant heights, the pseudostem circumference, number of leaves, number of days between planting and flowering, number of days between flowering and harvest and number of days from planting to harvest. These characteristics were measured at the flowering time. The production characteristics such as the bunch weigth, number of fruits, average weigth of the fruits, productivity, number of hands and weight, number, length and diameter of the fruits of the 2nd hand. The correlations between the characteristics studied varied for each genotype, but they all showed significant correlation between the bunch weight and the characteristics fruit weigth and productivity. The correlations involving all genotypes were predominantly positive and significant.